2002
DOI: 10.1002/cncr.10320
|View full text |Cite
|
Sign up to set email alerts
|

The specific role of isoflavones on estrogen metabolism in premenopausal women

Abstract: Cancer is a genetic disease of somatic cells. Tumor karyotypes are rarely normal, and most show multiple abnormalities of both number and structure. The first direct evidence for this concept of cancer came from studies of tumor‐specific translocations in leukemias and lymphomas, revealing the importance of oncogenes and the regulation of gene transcription in cancer. A second major source of information about human cancer genes is hereditary cancer. Genetic predisposition of the autosomal dominant type impose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 97 publications
2
56
0
Order By: Relevance
“…Studies examining the effect of a soy protein diet on the menstrual cycle have demonstrated a significant increase in follicular phase length and delay in menstruation, including suppression of midcycle surges of LH and FSH, which potentially may reduce the risk of breast cancer (Cassidy et al, 1994;Lu et al, 1996;Nagata et al, 1998;Kumar et al, 2002). Isoflavones have in fact received a great deal of attention due to their antiproliferative properties and these would support the protective effect against breast cancer in premenopausal women observed in the present study.…”
Section: Premenopausal Womensupporting
confidence: 66%
“…Studies examining the effect of a soy protein diet on the menstrual cycle have demonstrated a significant increase in follicular phase length and delay in menstruation, including suppression of midcycle surges of LH and FSH, which potentially may reduce the risk of breast cancer (Cassidy et al, 1994;Lu et al, 1996;Nagata et al, 1998;Kumar et al, 2002). Isoflavones have in fact received a great deal of attention due to their antiproliferative properties and these would support the protective effect against breast cancer in premenopausal women observed in the present study.…”
Section: Premenopausal Womensupporting
confidence: 66%
“…By competing with endogenous oestrogen for ERs, thereby reducing the bioavailability of endogenous oestrogen, isoflavones may hypothetically lower the risk of breast cancer in postmenopausal women [96]. Isoflavones may also increase the serum levels of sex hormone-binding globulin (SHBG) so decreasing the levels of free estradiol [96,97]. A meta-analysis, however, did not show significant effects of isoflavone consumption on the circulating reproductive hormone concentrations (including oestrogen and SHBG) in pre-and postmenopausal women.…”
Section: Breast Cancermentioning
confidence: 95%
“…Higher endogenous oestrogen concentration is associated with a higher risk of breast cancer development. By competing with endogenous oestrogen for ERs, thereby reducing the bioavailability of endogenous oestrogen, isoflavones may hypothetically lower the risk of breast cancer in postmenopausal women [96]. Isoflavones may also increase the serum levels of sex hormone-binding globulin (SHBG) so decreasing the levels of free estradiol [96,97].…”
Section: Breast Cancermentioning
confidence: 99%
“…In premenopausal women, on the other hand, soy protein may reduce circulating E2 concentration by inhibiting 17β-HSD1 activity in the ovaries. A number of human intervention trials, although not all [19], have found that high intake of either isoflavones or soy foods reduce blood E2 levels among premenopausal women [20][21][22][23]. We found in a previous report that the risk of endometrial cancer was reduced only among those whose daily intake of isoflavones was equal to or greater than 43 mg/day, particularly for those who consumed over 62 mg of isoflavones per day [4].…”
Section: Discussionmentioning
confidence: 86%
“…We found in a previous report that the risk of endometrial cancer was reduced only among those whose daily intake of isoflavones was equal to or greater than 43 mg/day, particularly for those who consumed over 62 mg of isoflavones per day [4]. Interestingly, the intervention trial with a significant finding was also mainly restricted to those with a higher supplementation level of isoflavones (> 100 mg/day) or those using a more potent form of isoflavone (genistein) [20,21,23]. In this study, we also found the interaction with genotype was only significant for soy isoflavones, but not soy protein, indicating that it is the phytoestrogen isoflavones from soy that play a major role.…”
Section: Discussionmentioning
confidence: 99%